IRON DEFICIENCY ANEMIA AND BODY MASS INDEX IN ADOLESCENT MENSTRUAL CYCLE - Sri Hidayati (Penelitian dan Pengembangan Ilmu, 2024)
The prevalence of anemia in the world is 46% according to WHO and 68% of women based on Riset Kesehatan Dasar experience irregular menstruation. Menstrual cycle disorders have an increased risk of cancer and cardiovascular disease. Anemia and nutritional status is one of the factors that can affect menstruation. The study was to determine the effect of anemia and Body Mass Index (BMI) on the menstrual cycle of young women. This type of research is observational analytic with a cohort study design. This study uses primary data. Initial data collection included measurements of body weight and height, blood sampling and questionnaires. The determination of anemia was carried out by examining blood samples with Hb Sahli. Determination of the menstrual cycle by filling out a questionnaire about menstruation for 3 months. Data analysis using a computer program with a 95% confidence level. Bivariate analysis using chi square with α 0.05. Multiple logistic regression is used to conduct multivariate analysis. The results showed 15% of female adolescents had anemia, 48.3% of body mass index was abnormal and 46.7% of menstrual cycle was abnormal. There is no influence of anemia and body mass index on menstruation for young women. Based on the results of the study, young women